2017
DOI: 10.1111/gcb.13648
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of N2O emission by manure application to agricultural soils may largely offset carbon benefits: a global meta‐analysis

Abstract: Animal manure application as organic fertilizer does not only sustain agricultural productivity and increase soil organic carbon (SOC) stocks, but also affects soil nitrogen cycling and nitrous oxide (N O) emissions. However, given that the sign and magnitude of manure effects on soil N O emissions is uncertain, the net climatic impact of manure application in arable land is unknown. Here, we performed a global meta-analysis using field experimental data published in peer-reviewed journals prior to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
114
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 265 publications
(166 citation statements)
references
References 98 publications
(127 reference statements)
16
114
4
2
Order By: Relevance
“…Some practices leading to C sequestration may increase emissions of trace greenhouse gases, especially N 2 O. For example, a recent global meta‐analysis of experiments with manure showed that, on average, manure addition increased N 2 O emission by 33% compared to inorganic N fertilizer and this could largely offset the benefit of increased SOC stock (Zhou et al., ). However, the trend was smaller with FYM than with manures containing a larger proportion of readily mineralizable N such as poultry manure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some practices leading to C sequestration may increase emissions of trace greenhouse gases, especially N 2 O. For example, a recent global meta‐analysis of experiments with manure showed that, on average, manure addition increased N 2 O emission by 33% compared to inorganic N fertilizer and this could largely offset the benefit of increased SOC stock (Zhou et al., ). However, the trend was smaller with FYM than with manures containing a larger proportion of readily mineralizable N such as poultry manure.…”
Section: Discussionmentioning
confidence: 99%
“…It is also in line with attempting to meet the UN Sustainable Development Goals (http://www.un.org/sustainabledevelopment/sustainable-development-goals. We also emphasize that SOC increases are not necessarily the key issue when considering the success of climate change mitigation through land management practices: the impacts of management changes on emissions of trace greenhouse gases, especially N 2 O, must be given equal weight (Smith et al., ; Zhou et al., ; Tian et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DLEM, N 2 O fluxes can be lower when plant N demand exceed N inputs, particularly in systems that are N limited, provided that other factors are not limiting (Lu et al, ). But as N inputs exceed N demand, excess N could ultimately lead to N saturation (Fisher et al, ) intensifying nitrification and denitrification rates resulting in an increase in N 2 O fluxes (Zhou et al, ). The thresholds at which these transitions occur in the DLEM largely depend on the prevalent PFTs, local climatic conditions, soil properties, land use history, and the N limitation at the site, which regulate soil microbial activities necessary for N cycling and transformation within the soil.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies that use default emission factor assume a linear increase in N 2 O emissions as a function of fertilizer/manure N application but do not account for the effect of soil conditions, climate, and vegetation type, which varies considerably across different regions (Philibert et al, 2012;Stehfest & Bouwman, 2006). Recent studies have contended that fertilizer/manure inputs lead to linear, exponential, or hyperbolic response of soil N 2 O emissions to N applications (Bouwman et al, 2002;Hoben et al, 2011;Shcherbak et al, 2014;Zebarth et al, 2008;Zhou et al, 2017), depending on whether the soil substrate is N limited or carbon limited (Kim et al, 2013). For example, in a recent meta-analysis study, Shcherbak et al (2014) found that N 2 O fluxes increased significantly faster compared to linear responses following mineral N application for most crop types.…”
Section: Global Nitrous Oxide Emissions and Its Comparison With Previmentioning
confidence: 99%